Predicted Glycaemic Index of Food Formulated using Native and Modified Sago (Metroxylon sagu) Starches - Mohd Alhafiizh, Zailani; Kamilah, H.; Awang Ahmad Sallehin, Awang Husaini; Awang Zulfikar Rizal, Awang Seruji; Shahrul Razid, Sarbini (2022)
The formulation of starch-based food focus on improving its functional food properties which can benefit human health. This includes the enhancement of starch properties as an ingredient to provide low glycaemic index food. Consumption of this food will benefit obese and diabetic individuals (Bello-Pérez et al., 2021). It can be achieved by producing a starch with low digestibility by increasing the resistant starch (RS) content of the starch. Examples of starches developed to exhibit low glycaemic indexes are maize and cassava starches (Bello-Pérez et al. 2021; Eyinla et al., 2021). As starch is already introduced in food formulations like fish crackers, the addition of RS in food formulation gives a promising alternative in the production of products with better functional food properties. Sago starch which contains a high RS is a promising candidate (Arshad et al., 2018). There is scarce information on sago starch formulated in food products especially its digestibility and potential prebiotic properties. Thus, this study investigated the functional food properties of food formulated with sago starch and its derivatives.